Linguistic insights into customer satisfaction: an exploratory analysis of online reviews for gaming destination resorts in Las Vegas - Lee, Harold Sang Kwon; Wang, Jue; Moreno-Brito, Yahaira Lisbeth; Shen, Yiwen; Kim, Hak Seon (Journal of Hospitality and Tourism Technology, 2025)
Purpose: This study aims to explore the quality of user-generated content regarding readability, polarity, word length and diversity, as well as its implications for guest satisfaction in Las Vegas luxury gaming resorts. Design/methodology/approach: This study examined 12,940 textual customer reviews from six luxury hotels in luxury gaming destination resorts via Google Travel gathered from SCTM 3 (Smart Crawling and Text Mining). Moreover, the regression analysis identified the relationship between the variables in the textual customer reviews and the customer’s overall satisfaction. Findings: A key finding of this study revealed that word length moderates the relationship between readability and overall customer satisfaction negatively, whereas it positively moderates the path from sentiment polarity and diversity to overall customer satisfaction. Originality/value: This study contributes to the relationship between technical aspects of online reviews. The adopted methodology allows us to precisely identify the essential attributes that influence customer satisfaction through textual reviews. Further, the study explores the quality of user-generated content, addressing aspects such as readability, polarity, diversity and word length, providing a unique perspective on how these specific elements directly impact customer satisfaction in this context of hotels in luxury in Las Vegas.
Keywords: Customer satisfaction; Gaming destination resort; Las Vegas; Online review; Sentiment polarity; Textual customer review